Postur Kerja Saat Mengukur dan Menjahit Jok Mobil Dengan Metode RULA - Erniyani, Erniyani; Ramdhani, Irin; Raodah, Raodah (Universitas Muhammadiyah Sorong, 2024)
Activities that are carried out repeatedly over a long period will result in musculoskeletal disorders. As happened, company X focuses on the production of car seats. The results of interviews with workers revealed that they often experienced complaints in the back, neck, feet, and calves. Therefore, this research aims to analyze workers' body posture, especially in the measuring and sewing department, to increase work comfort and productivity using the Rapid Upper Limb Assessment (RULA) method. The research results show that the final score obtained from the measuring position using the RULA method gets the same score, namely 5. This means that the score is at a high level with investigative and corrective actions immediately handled. The body posture involved when measuring a car seat in a less-than-optimal position is (1) bent or flexed neck. This position often puts pressure on the neck muscles to get a better angle, causing muscle fatigue due to long and repetitive work; (2) the worker's back bends forward to access certain parts of the car seat, especially if done in low or difficult-to-reach areas. This position can increase the load on the spine and cause discomfort and even injury to the lower back; (3) raised shoulders, due to the worker measuring the top or accessing a higher area of ​​the car seat which will constantly increase the risk of neck and shoulder muscle tension; (4) the arms are bent and the hands are repetitive, this position occurs due to seat measurements which require repeated use of the hands to mark certain areas.